Impact of Structured Debates on Nigerian Secondary School Students’ Reading Outcomes and Reading Anxiety - Vincent Ugah Uguma; Alexander Timothy; Eucharia Obiageli Obiekezie; Virginia Emmanuel Ironbar; Gladys Denis Ukume; Francis Ademola Sanda; Grace Onya Edu; Ozioma Odirachimma Okoye; Iwuala Patricia Ebere Chilebe; James E. Archibong; Miebaka Nabiebu; Otemdam Jombo Okey (Ianna Journal of Interdisciplinary Studies, 2024)
Background: Reading proficiency is crucial for academic success, yet many students struggle with comprehension, do not engage in independent, self-motivated reading, and lack confidence in their reading abilities. The absence of a reading culture in Nigeria threatens the knowledge economy, as those who lack reading proficiency are incapable of producing, accessing, or transmitting knowledge.